A 2-Year Follow-Up Study of Patients On Continuous Ambulatory Peritoneal Dialysis (CAPD) In Specialized Hospitals In Dhaka, Bangladesh - Arefin, Mohammad Shakib Uz Zaman; Islam, Md Nazrul; Ahmed, Parvez Iftekhar; Rashid, Harun Ar (Journal of Dhaka Medical College, 2016)
Continuous Ambulatory Peritoneal Dialysis (CAPD) is an established form of dialysis in Bangladesh now-a-days. It was a retrospective analysis, where we studied on 107 cases of CAPD patients in different specialized hospitals in Dhaka, Bangladesh. The aim of this study was to describe experience of CAPD in our setup and its impact on survival.Male and female ratio was 54:53.Mean age was 60±11.2years. Main causes of ESRD were diabetic nephropathy (58.9%).53.3% of patient prefered CAPD as a mode of renal replacement therapy to other modalities.32.7% patient suffered from peritonitis. Exit site infection occurred in 9.3%. Among non- infectious complications pain during dialysis(30.8%) was most common. Mean Blood urea was 19.15mg/dl; serum creatinine 633micromol/L. J Dhaka Medical College, Vol. 24, No.2, October, 2015, Page 132-135